The contribution of mental health and gender attitudes to intimate partner violence in the context of war and displacement: Evidence from a multi-informant couple survey in Iraq. (September 2019) - Goessmann, Katharina; Ibrahim, Hawkar; Saupe, Laura Bebra; Ismail, Azad Ali; Neuner, Frank
Abstract: Rationale: Intimate partner violence is a prevalent issue in refugee and internally displaced populations in post-war and migration settings including camps in the Middle East. In this context, partner violence has been associated with war-related trauma, camp factors, individual characteristics, and gender attitudes. Objective: With a dual-informant survey among a sample of Iraqi couples residing in a camp for displaced people in the Kurdistan Region of Iraq ( N = 92) this study investigated the relationship between war-related psychopathology, attitudes towards women, and male-perpetrated partner violence. Method: Moderated regression analysis was applied using information from both partners to predict partner violence reported by wives. Results: Over 58% of the women in this sample reported past-year exposure to partner violence. Further analyses revealed significant main effects of men's self-reported psychopathology (posttraumatic stress disorder and depression) and their own gender attitudes on partner violence. In a multivariate regression, moderating effects were found, as higher psychopathology levels and inequitable gender attitudes in men interacted in the prediction of male-perpetrated partner violence. Conclusions: This study highlights the high prevalence of partner violence among Iraqi displaced women. In addition, the results show an interplay of several violence-impelling factors in war-affected men. This emphasizes the importance of addressing both mental health issues and gender attitudes in the efforts to reduce or end violence against women in post-war settings. Highlights: Intimate partner violence (IPV) is common among displaced women in Iraq. Displaced men report high levels of war exposure and trauma-related psychopathology. Men's mental health and gender attitudes interact in prediction of their wife's IPV.